The Purpose and Objectives of the Armenian Electronic Proofreading System - HAKOBYAN, FRIDA (Bulletin of Yerevan University B: Philology, 2021)
The purpose of the article is to present the principles of creating the Armenian Electronic Proofreading System. The necessity of a new Proofreading program is underlined, because even though there are a few spell and grammar checkers, they are incomplete, as they do not correct all types of mistakes. For the creation of a new Proofreading program, the importance of including rich vocabulary and formal description of the language are highlighted. The newly-created program is supposed to correct spelling, grammar, punctuation and stylistic errors. The Armenian Electronic Proofreading program will highly contribute to the use of computer technology in the field of linguistic research, elimination of errors in texts through computer programs, as well as to the successful use of the Armenian language as a web language.